Dynamic behavior of a masonry bell tower subjected to actions caused by bell swinging - Nochebuena-Mora, Elesban (2021)
Seismic response of masonry towers has been widely studied, whereas research on their behavior under other dynamic forces is not common. The aim was to study the dynamic effects of bell swinging on a masonry tower, evaluating the response through different approaches. For this purpose, the south tower of the National Palace of Mafra was adopted due to its slenderness and its four swinging bells located at 49 m height. Dynamic identification tests allowed to determine the tower’s dynamic properties aimed at calibrating a numerical model. Frequency analyses assessed possible resonance effects by comparing the frequencies of the excitations with those of the tower. Nonlinear dynamic analyses evaluated the response in terms of displacements and cracking, while nonlinear static analyses determined damage patterns assuming different load combinations. Variations of structural stiffness and intensity of the forces were also studied. The results demonstrated that the tower, subjected to bells action, remains within the elastic range with a high safety level. Moreover, crack patterns correspond to local damage, which do not compromise the stability of the structure. Finally, parametric analysis allowed to obtain equivalent static load factors for bells of the Spanish system.